Four value-adding algorithms. - Even, S.
Israel is far advanced in computer science research, an area its universities have worked in since the 1950s. In particular, its academics have developed algorithms now in use everywhere for data compression, encryption, proof of identification, and much else. The author outlines compression schemes including Huffman codes and the Lempel-Ziv solution. Randomised algorithms are discussed as is checking a prime. The author then discusses the electronic wallet (EFT based systems using magnetic cards) and the cryptography involved. The Fiat-Shamir ID protocol is also discussed
Keywords: EFT based systems; Fiat-Shamir ID protocol; Huffman codes; Lempel-Ziv solution; Cryptography; Data compression; Electronic wallet; Encryption; Magnetic cards; Proof of identification; Randomised algorithms; Value-adding algorithms